Analisis Pengaruh Kemasan Produk Belanja Online Terhadap Jumlah Sampah Plastik di Indonesia - Putri, Frisca Herlia; ., Sudarti; ., Yushardi (CV. ITTC INDONESIA, 2023)
Trash is the residue or byproduct of human activities that no longer has economic value, in other words, it is not usable. About 21.1 million tons of trash are generated every year in Indonesia. This trash can come from households or industries. There are two types of trash, organic and inorganic trash. Plastic is one type of inorganic trash. This plastic trash can cause soil pollution because it cannot decompose and can affect soil fertility. With the advancement of technology, many people in Indonesia are starting to shop online, which also affects trash management, especially plastic trash, as it is widely used in online packaging, most of which use bubble wrap. In some areas in Indonesia packaging generates more plastic trash than other types of trash. This article discusses packaging trash from the Indonesian online shopping industry. The research method used in this article is a literature review, which is a way to read, study, and understand something from various sources. Research conducted allows us to understand the impact of increased use of plastic packaging in e-commerce product distribution.